Kondisi Sosial Ekonomi Masyarakat Buruh Industri Menghadapi Pandemi Covid-19 di Kota Makassar - Suardi Suardi; Herdiyanti Ramlan; Kiki Reskiana (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2022)
The covid-19 pandemi has changed the social conditions in various countries, including Indonesia, especially in the city of Makassar. Almost all people in the city of Makassar have problems with their economic system. The COVID-19 pandemi has given rise to problems for industrial workers/laborers, with the presence of the COVID-19 pandemi there are several industries that have terminated work rights (PHKs), were laid off to reduce salaries, so that the working community experienced problems in their socio-economic status due to missing and problematic jobs. The results of this study are that the labor community has experienced layoffs (Termination of Work Rights), at home and the reduction of the pilgrimage, it is true that the labor community has lost their jobs and has difficulty meeting their needs, survival strategies, in facing a problem especially this problem is a big problem of course someone must have a strategy in order to survive in that era. The strategy carried out by the community is to carry out social strategies and marketing strategies.